2013
DOI: 10.3109/07420528.2013.807275
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of the renin-angiotensin-aldosterone system in dogs: relation to blood pressure and renal physiology

Abstract: The renin-angiotensin-aldosterone system (RAAS) plays a pivotal role in the regulation of blood pressure and volume homeostasis. Its contribution to the development of cardiovascular diseases has long been recognized. Extensive literature has shown that peptides of the RAAS oscillate with a circadian periodicity in humans, under strong influence of posture, sleep, and age. Although observations of time-variant changes in the renin cascade are available in dogs, no detailed chronobiological investigation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 62 publications
4
52
0
Order By: Relevance
“…Another limitation is the potential effects of chronobiology and diet on the RAAS and NP system. Circadian fluctuations of RAAS hormones and dietary sodium content could have affected our results, but intrapatient variables (feeding times, food types, sample collection times) were held constant for the duration of the study period 55, 56. Pooled urine samples also were used to minimize the potential effect of these variables on urinary aldosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the potential effects of chronobiology and diet on the RAAS and NP system. Circadian fluctuations of RAAS hormones and dietary sodium content could have affected our results, but intrapatient variables (feeding times, food types, sample collection times) were held constant for the duration of the study period 55, 56. Pooled urine samples also were used to minimize the potential effect of these variables on urinary aldosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor which could affect results is time‐to‐time variation. In dogs, circadian variation has been shown for serum cortisol45 and plasma renin activity,46 but has not been investigated for plasma ET‐1. In a small human study, time‐to‐time variation in ET‐1 was found 47.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Renin-angiotensin system (RAS) activity is an important modulator of blood pressure and plays a key role in renal diseases (Mochel et al, 2013). In the kidney, the RAS regulates renal cell growth and contributes to elevated transforming growth factor β production, leading to fibrosis (RuizOrtega and Egido, 1997).…”
Section: Introductionmentioning
confidence: 99%